PENGEMBANGAN LKPD BERBASIS AJARAN TAMANSISWA TRI-N MUATAN BAHASA INDONESIA KELAS II DI SD N PUREN - Yulianto; Siti Anafiah; Biya Ebi Praheto (Universitas Sarjanawiyata Tamansiswa, 2022)
This descriptive study aims to describe the development and feasibility of LKPD based on the teachings of Tamansiswa Tri-N content in Indonesian for class II at SD N Puren. The research method used in this study is the Borg and Gall model development method which has been modified by Hasyim and is only limited to seven research and development steps, namely: 1) potential and problems, 2) data collection, 3) product design, 4) product validation. , 5) product revision, 6) product trial, 7) product revision. Data collection techniques in the form of observation, interviews and questionnaires with a set of written statements or questions to respondents to answer. The results of this development research indicate that the LKPD product based on the teachings of Tamansiswa Tri-N Class II Indonesian language content at SD N Puren has been successfully developed. The feasibility of the LKPD product obtained an average feasibility score of 93.3% by material experts and 80% by media experts. Then the results of the questionnaire that was tested in the field to determine the response of the school, namely the second grade teacher obtained an average score of 99.09%. While the test of student response questionnaires obtained an average score of 99.70%. Thus, the development of LKPD products based on the teachings of Tamansiswa Tri-N containing Indonesian class II at SD N Puren has good quality to help students learn.